1982
DOI: 10.1002/ijc.2910290316
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐reactions between tumor cells and allogeneic normal tissues. inhibition of a syngeneic lymphoma outgrowth in h‐2 and non‐h‐2 alloimmune balb/c mice

Abstract: To test whether alloimmunization with H-2 or/and non-H-2 different normal tissues may increase the immunity to syngeneic tumors, groups of BALB/c (H-2d) mice were immunized with a series of allogeneic lymphoid cells and then challenged i.p. with syngeneic lymphoma cells. The outgrowth of otherwise lethal doses of the Moloney virus-induced lymphoma YC8 and of its clones was inhibited in BALB/c mice immune to DBA/2 (H-2d), C3Hf (H-2k), C3H.SW (H-2b), C3H.OH (H-2o2) and to B10 background tissues but not in mice i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

1982
1982
1990
1990

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 32 publications
4
14
0
Order By: Relevance
“…Cytotoxic T lymphocytes (CTL) were able to lyse YC8 cells and DBA/2 or B10.D2 blasts while having little or no effect on several other syngeneic or allogeneic tumor or blast cells. These experiments confirm the presence on the surface of YC8 cells of DBA/2-1ike MiHA, a subset of which is shared with B10 background, a conclusion in keeping with previous transplantation studies in BALB/c anti-DBA/2 immune mice and by in vitro clonal analysis with anti-DBA/2 CTL [15,22]. In addition, we have recently found that such MiHA can also be defined by appropriate BALB/c anti-DBA/2 antisera (Ballinari et al submitted for publication).…”
Section: Immunotherapeutic Ability Of Balb/c Anti-yc8 Effector Cellssupporting
confidence: 87%
“…Cytotoxic T lymphocytes (CTL) were able to lyse YC8 cells and DBA/2 or B10.D2 blasts while having little or no effect on several other syngeneic or allogeneic tumor or blast cells. These experiments confirm the presence on the surface of YC8 cells of DBA/2-1ike MiHA, a subset of which is shared with B10 background, a conclusion in keeping with previous transplantation studies in BALB/c anti-DBA/2 immune mice and by in vitro clonal analysis with anti-DBA/2 CTL [15,22]. In addition, we have recently found that such MiHA can also be defined by appropriate BALB/c anti-DBA/2 antisera (Ballinari et al submitted for publication).…”
Section: Immunotherapeutic Ability Of Balb/c Anti-yc8 Effector Cellssupporting
confidence: 87%
“…It has also been reported that the frequency of these antitumor responses could be increased by in vitro stimulation of patient PBL (Pt-PBL) with autologous tumor cells or with allogeneic normal lymphocytes [15,17,19,23]. The possibility of increasing an autologous killing of cancer cells by alloimmunization, and the demonstration that a similar phenomenon may occur with different types of experimental tumors [10,12,14], prompted us to investigate whether in vitro ailosensitization of PBL could activate the killing of autologous malignant melanoma, a tumor which has received little attention in this respect in the previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…These findings further substantiate the presence of non-H-2 antigens of DBA/2 background on YC8 tumor cells. Altogether, the specificity of the blocking by OR-1, the pattern of CTL reactivity and its similarity with that obtained by histogenetic studies (Sensi et al, 1984;Parmiani et al, 1982) indicate that the antigens involved in these cross-reactions are MiHA of the DBA/ 2 background.…”
Section: Discussionmentioning
confidence: 56%
“…Previous work from our laboratory has shown a cross-reaction between the Moloney virus-induced BALB/c lymphoma YC8 and the non-H-2 alloantigens of DBA/2 tissues (Parmiani et al, 1982;Sensi et al, 1983Sensi et al, , 1984. It was of interest, therefore, to attempt to develop an antiserum directed against multiple MiHA of DBA/2 background to further analyze this phenomenon at the serological level and, if possible, to characterize the molecules involved.…”
mentioning
confidence: 96%